Prevalence and Risk Factors of Anxiety Among Secondary School Children in Diyala Province - Rusul Mohammed Kareem; Mehdi Shemkhi Jebr (Al-Turath Journal of Nursing, 2026)
Background: Emotional disorders are common among adolescents and arise from interacting social, psychological, biological, familial, and environmental factors. Epidemiological data suggest that about 7.5% of Iraqi adolescents fulfil diagnostic criteria for anxiety disorders. Aim of study: To assess the prevalence of anxiety symptoms among children aged 12-19 in Diyala province and to assess associated factors. Subjects and Methods: A cross-sectional study with analytic components conducted in eleven intermediate and secondary schools in Diyala City during a period of six months (October/1/2025 – April/1/2026). It included 537 intermediate and secondary school students aged between 12 - 19 years. We used a SCARED scale of child anxiety which is a widely used tool for assessing anxiety. Data was collected by self-administered questionnaire including sociodemographic, clinical and school-related, and psychosocial and trauma characteristics. Results: In this study, mean anxiety score was 29.75 ± 13.11, with a range of 0 to 76. Notably, a significant portion of the distribution lies above the clinical cutoff point of 25 with a prevalence of 66.1%. Generalized anxiety represents the most prevalent specific subtype at 62%. Seven factors remained significantly associated with child anxiety, these factors were exposure to bullying, family conflict or violence, difficulties in healthcare accessibility, insufficient family income, having chronic disease, female gender, and secondary educational level. Conclusion: The prevalence of anxiety among school children in Diyala Province was high. The most common subtype was generalized anxiety, followed by social anxiety and panic/somatic symptoms. The independent associated factors of anxiety were female gender, exposure to bullying, family conflict or violence, difficult healthcare accessibility, insufficient family income, chronic disease, and secondary educational level..